2018
DOI: 10.1111/jhn.12571
|View full text |Cite
|
Sign up to set email alerts
|

‘For me it's about not feeling like I'm on a diet’: a thematic analysis of women's experiences of an intermittent energy restricted diet to reduce breast cancer risk

Abstract: Many participants found intermittent dieting preferable to previous experiences of continuous dieting. The findings provide some insight into the ways in which intermittent dieting is successful, and why it could be considered a viable alternative to continuous energy restriction for weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…29 Additionally, the term “diet” can sometimes have negative connotations and suggest a departure from one’s usual eating habits. 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Additionally, the term “diet” can sometimes have negative connotations and suggest a departure from one’s usual eating habits. 30…”
Section: Discussionmentioning
confidence: 99%
“…29 Additionally, the term "diet" can sometimes have negative connotations and suggest a departure from one's usual eating habits. 30 To help female cancer survivors follow dietary recommendations that promote healthy cancer survivorship and fertility, one effective strategy is to combine evidence-based dietary patterns with effective nutrition counseling strategies such as motivational interviewing, self-monitoring, social support, goal setting, group counseling and cognitive restructuring. 31 Most often, multiple nutrition counseling strategies would need to be integrated to achieve results.…”
Section: Perceived Rigidity Of Dietary Guidancementioning
confidence: 99%
“…Besides energetic restriction as a promising approach to not only lose weight but to also benefit cognition and brain structure (51,55,56) , dietary modifications that do not explicitly involve fasting may be easier to adopt for most individuals (57) . In a cross-sectional epidemiological analysis in >8000 adults, we found that less animal-based dietary intake (resembling vegetarian and vegan diets and those similar to Mediterranean diet) was linked to better weight status and to certain differences in personality traits, i.e.…”
Section: Diet and Brain Healthmentioning
confidence: 99%
“…In this regard, alternative methods have been suggested as appropriate dietary regimens, including intermittent energy restriction (IER) as an umbrella term that includes two different subtypes of fasting: intermittent fasting (IF) and time-restricted feeding (TRF) [ 4 ]. Intermittent fasting (IF) involves short periods of marked energy restriction followed by periods of usual caloric intake [ 6 ].…”
Section: Introductionmentioning
confidence: 99%